The Life of a song the social structure of the music production process of an independent band in the Metro Manila music industry (May 2017) - Onday, Adrienne C. (2022)
This research aims to understand the specific roles and tasks of the division of labor in the local independent music industry and highlight the existence of collective action that creates its social structure. From in-depth interviews during the production process with a local band and their sound engineer, three categories of roles emerged: instrument-based, non-musical, and non-member roles. These roles and their interactions are mediated by six elements: preexisting relationships, comfortability, know-how/expertise, consensus, spontaneity, and professionalism and professionalization. Ultimately, we find that band members are not merely concerned with performance but also with various responsibilities required for the sustenance and organization of the band; and that supporting roles, particularly that of sound engineers, are necessary in creating music goods. The study also suggests that despite using the family as the basic framework of organization, the band dynamic heavily features spontaneity in order to bridge pre-existing and professional relationships.
Keywords: Bands (Musical groups); Composition (Music); Filipino musicians -- Interviews; Music and society; Music industry